Pengembangan Bahan Ajar Tematik Berbasis Islam & Kearifan Lokal Kelas Iv Min Seduri & Mis Nurul Amal Kabupaten Mojokerto - Benny Angga Permadi; Ika Agustin Adityawati (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2018)
The Development of Thematic Teaching Materials Islam and Local Wisdom Based Class IV of MIN (Madrasah Ibtidaiyah Negeri (State of Islamic Elementary School)) Seduri and MIS (Private of Islamic Elementary School) Nurul Amal Mojokerto Regenct. The application of curriculum 2013 requires every student of elementary school from first up to sixth graders to apply thematic study. The interview with the teacher of fourth grader of MIN (Madrasah Ibtidaiyah Negeri (State of Islamic Elementary School)) Seduri and MIS (Private of Islamic Elementary School) Nurul Amal Mojokerto Regency and also the observation in the field show that the teaching materials used from Ministry of Education and Culture of the theme of ‘My Place’ is not fit in with the condition of students’ place in Mojokerto Regency while the essence of curriculum 2013 of thematic study is to support the contextual aspect and close with students’ place. Else, the character education in curriculum 2013 must also be applied through Islamic habits which are done in school. These habits are not discussed in guide book from Ministry of Education and Culture. Therefore, this research objective is to develop the product of thematic teaching materials Islamic and local wisdom based. The feasibility of teaching materials which are developed is assessed according to the validity, interesting, effectiveness and application levels. The research result and development of thematic study materials are in form of (1) thematic teaching materials Islamic and local wisdom based. The materials are integrated with Islamic values in the teaching and learning activities and the materials about local wisdom of Mojokerto Regency such as historical buildings, special foods, dances and handicrafts. (2) the experts validity shows percentage of 89.17% with the criteria of high validity and deserved to be used. (3) the interesting level shows percentage of 93.12% with the criteria of high interesting and deserved to be used. (4) the effectiveness level shows percentage of 78.01 with the criteria of high effective. (5) application level shows percentage of 86.08% with the criteria of very good and fulfil the elements of application for teaching materials.